Simultaneous determination of warfarin and 7-hydroxywarfarin in rat plasma by HPLC-FLD - Zayed Aref; Babaresh Wahby M.; Darweesh Ruba S.; El-Elimat Tamam (Acta Pharmaceutica)
In this study, high-performance liquid chromatography with fluorescence detection (HPLC-FLD) has been used for the first time, for direct determination of warfarin and its major metabolite, 7-hydroxywarfarin, in rat plasma. The simple and sensitive method was developed using Fortis® reversed-phase diphenyl column (150 × 4.6 mm, 3 μm) and a mobile phase composed of phosphate buffer (25 mmol L−1)/methanol/acetonitrile (70:20:10, V/V/V), adjusted to pH 7.4, at a flow rate of 0.8 mL min−1. The diphenyl chemistry of the stationary phase provided a unique selectivity for separating the structurally related aromatic analytes, warfarin and 7-hydroxywarfarin, allowing their successful quantification in the complex plasma matrix. The method was linear over the range 0.01–25 μg mL−1, for warfarin and 7-hydroxywarfarin, and was found to be accurate, precise and selective in accordance with US FDA guidance for bioanalytical method validation. The method was sensitive enough to quantify 0.01 μg mL−1 of warfarin and 7-hydroxywarfarin (LLOQ) using only 100 μL of plasma. The applicability of this method was demonstrated by analyzing samples obtained from rats after oral administration of a single warfarin dose, and studying warfarin and 7-hydroxywarfarin pharmacokinetics.